Frequent Detection of Undiagnosed HIV Within Emergency Departments in Botswana. Issue 7 (July 2021) - Pintye, Jillian; Ortblad, Katrina F.; Mawandia, Shreshth; Bakae, Odirile; Tau, Lenna; Grande, Matias; Mogomotsi, Goabaone Panky; Mmatli, Esther; Ngombo, Modise; Norman, Tebogo; Seckel, Laura; Ledikwe, Jenny
Abstract : Abstract: Among 130, 161 HIV testing records from unique individuals at 149 programmatic sites in Botswana, frequency of detecting undiagnosed HIV infection within emergency departments (EDs) was 4.7% (455/9695), 2-fold higher than other clinic-based HIV counseling and testing. Men and noncitizens less frequently initiated same-day antiretroviral therapy after testing HIV positive within emergency departments. Abstract : We evaluated the frequency of detecting undiagnosed HIV infection in emergency departments using 130, 161 HIV testing records from unique individuals at 149 sites in Botswana's national HIV testing program.